Imetelstat in patients with lower-risk myelodysplastic syndromes who have relapsed or are refractory to erythropoiesis-stimulating agents (IMerge): a multinational, randomised, double-blind, placebo-controlled, phase 3 trial - Platzbecker, Uwe; Santini, Valeria; Fenaux, Pierre; Sekeres, Mikkael A; Savona, Michael R; Madanat, Yazan F; Díez-Campelo, Maria; Valcárcel, David; Illmer, Thomas; Jonášová, Anna; Bělohlávková, Petra; Sherman, Laurie J; et al. (Lancet, 2024)
BACKGROUND: Unmet medical needs remain in patients with red blood cell transfusion-dependent (RBC-TD) lower-risk myelodysplastic syndromes (LR-MDS) who are not responding to or are ineligible for erythropoiesis-stimulating agents (ESAs). Imetelstat, a competitive telomerase inhibitor, showed promising results in a phase 2 trial. We aimed to compare the RBC transfusion independence (RBC-TI) rate with imetelstat versus placebo in patients with RBC-TD LR-MDS. METHODS: In phase 3 of IMerge, a double-blind, placebo-controlled trial conducted in 118 sites including university hospitals, cancer centres, and outpatient clinics in 17 countries, patients (aged ≥18 years) with ESA-relapsed, ESA-refractory, or ESA-ineligible LR-MDS (low or intermediate-1 risk disease as per International Prognostic Scoring System [IPSS] criteria) were randomly assigned via a computer-generated schedule (2:1) to receive imetelstat 7·5 mg/kg or placebo, administered as a 2-h intravenous infusion, every 4 weeks until disease progression, unacceptable toxic effects, or withdrawal of consent. Randomisation was stratified by previous RBC transfusion burden and IPSS risk group. Patients, investigators, and those analysing the data were masked to group assignment. The primary endpoint was 8-week RBC-TI, defined as the proportion of patients without RBC transfusions for at least 8 consecutive weeks starting on the day of randomisation until subsequent anti-cancer therapy, if any. Primary efficacy analyses were performed in the intention-to-treat population, and safety analyses were conducted in patients who received at least one dose of trial medication or placebo. This trial is registered with ClinicalTrials.gov (NCT02598661; substudy active and recruiting). FINDINGS: Between Sept 11, 2019, and Oct 13, 2021, 178 patients were enrolled and randomly assigned (118 to imetelstat and 60 to placebo). 111 (62%) were male and 67 (38%) were female. 91 (77%) of 118 patients had discontinued treatment by data cutoff in the imetelstat group versus 45 (75%) in the placebo group; a further one patient in the placebo group did not receive treatment. Median follow-up was 19·5 months (IQR 12·0-23·4) in the imetelstat group and 17·5 months (12·1-22·7) in the placebo group. In the imetelstat group, 47 (40% [95% CI 30·9-49·3]) patients had an RBC-TI of at least 8 weeks versus nine (15% [7·1-26·6]) in the placebo group (rate difference 25% [9·9 to 36·9]; p=0·0008). Overall, 107 (91%) of 118 patients receiving imetelstat and 28 (47%) of 59 patients receiving placebo had grade 3-4 treatment-emergent adverse events. The most common treatment-emergent grade 3-4 adverse events in patients taking imetelstat were neutropenia (80 [68%] patients who received imetelstat vs two [3%] who received placebo) and thrombocytopenia (73 [62%] vs five [8%]). No treatment-related deaths were reported. INTERPRETATION: Imetelstat offers a novel mechanism of action with durable transfusion independence (approximately 1 year) and disease-modifying activity for heavily transfused patients with LR-MDS who are not responding to or are ineligible for ESAs. FUNDING: Janssen Research & Development before April 18, 2019, and Geron Corporation thereafter.
Keywords: Adolescent; Treatment Outcome; myelodysplastické syndromy; oligonukleotidy; lidé; Adult; Antineoplastic Combined Chemotherapy Protocols; dospělí; erytropoéza; Female; Myelodysplastic Syndromes; Erythropoiesis; výsledek terapie; Male; protokoly protinádorové kombinované chemoterapie; ženské pohlaví; trombocytopenie; Humans; Oligonucleotides; mužské pohlaví; Double-Blind Method; Thrombocytopenia; mladiství; dvojitá slepá metoda